(untitled) (Journal of Global Arts Studies, 2024)
Background: The enameled ceramics art of Chaoshan temples, as a distinctive traditional art form, occupies an important position within local culture and religious belief systems. With the growing emphasis on traditional culture in modern design fields, the Taoist cultural symbols embodied in enameled ceramics art have gradually attracted widespread scholarly and artistic attention. Objective: This study aims to conduct an in-depth analysis of Taoist cultural symbols in Chaoshan temple enameled ceramics art, exploring its craft characteristics, cultural significance, and possibilities for modern inheritance and innovation. Methods: Through the systematic organization and analysis of the materials, production techniques, and symbolic expressions of enameled ceramics art, this study reveals the specific manifestations of Taoist symbols and their deep integration with local culture. Furthermore, the research discusses how enameled ceramics art constructs a unique visual language and cultural identity through concepts related to Feng Shui and the Five Elements. Results: The findings indicate that Taoist symbols in enameled ceramics art, including dragons, phoenixes, mythical beasts, and talismanic motifs, embody philosophical ideas such as “following the natural way,” “understanding the Tao,” and “cultivating virtue,” reflecting the integration of religious belief and visual culture. Although the inheritance of enameled ceramics art faces challenges in contemporary society, innovative applications and global dissemination provide opportunities for breaking through traditional limitations and achieving modern development. Conclusion: Chaoshan temple enameled ceramics art plays an important role at the intersection of tradition and modernity. Its revitalization in contemporary society not only deepens the understanding of Taoist cultural symbols within local architectural art but also offers valuable insights into the inheritance and innovation of traditional art in modern society, demonstrating unique developmental potential and cultural value in contemporary spatial design.